THE PRACTICE OF READING AL-QUR'AN AMONG ISLAM YOUTHS - Ismail, Faisal Bin Husen; Sabirin, S; Zahari, Wan Ainaa Mardhiah Bin Wan; Rouzi, Kana Safrina; Kirin, Arwansyah Bin (Universitas Muhammadiyah Surakarta, 2022)
The practice of reading the Quran is decreasing among teenagers. Various activities have been carried out to encourage teenagers to read the Quran more often. The study was conducted to achieve the objective of identifying the level of frequency of Muslim teenagers reading the Al-Quran as well as examining the level of mastery of Muslim teenagers in reading the Al-Quran. This study was conducted qualitatively. The primary data source of the study is through observation and questionnaires to students of Tun Hussein Onn University Malaysia. A total of 72 respondents among Tun Hussein Onn University students were involved in this study. This sampling technique was chosen purposefully and was not based on probability. We aim the scope of this study at teenagers. The targeted age is individuals between the ages of 16 and 24, comprising Muslim teenagers only. We obtained secondary data sources through libraries, official reports and all related documents. This study found that the level of Quran reading among teenagers is at a moderate level. The level of mastery of the Qur'an is moderate to good according to findings. In addition, this study also found that there are not many young Muslims who master the knowledge of tajwid well. So, this study suggests a study on the level of teacher satisfaction with mastery and appreciation of the Quran among Muslim teenagers. We hope that Muslim teenagers, as well as the government and parents, as well as the media, give better attention and focus to the Quran.